Plasma-polymerized acetylene nanofilms modified by nitrogen ion implantation - Santos, D. C R; Mota, Rogério Pinto [UNESP]; Honda, R. Y. [UNESP]; Cruz, N. C. [UNESP]; Rangel, E. C. [UNESP] (Elsevier, 2013)
Thin films were prepared by plasma enhanced chemical vapour deposition (PECVD) from a mixture of acetylene and argon, and post deposition-treated by plasma immersion ion implantation (PIII). The effect of PIII on the nanofilms properties was evaluated as a function of treatment time. The average thickness and roughness were diminished upon PIII. On the other hand, hardness (0.7-3.9 GPa) and elastic modulus (29-54 GPa) increased upon 60 min of ion bombardment. Such results are ascribed mainly to the densification of the film structure caused by the increment in the crosslinking degree with increasing the energy deposited in the films. Wettability of the samples, investigated by contact angle measurements, was reduced (from 64 to 21°) right after PIII. This result, attributed to the introduction of polar groups in the film structure, was not preserved as the sample was aged in atmosphere. After aging, contact angles were larger than 70° but still smaller than 90°. Although the wettability has decreased with aging, the hydrophilic character of the samples was preserved. For certain treatment times, nitrogen PIII turned the plasma-polymerized acetylene films smoother, denser, mechanically and tribologicaly more resistant than the as-deposited material. © 2013 Elsevier B.V.
Keywords: Acetylene; Hardness; Ion implantation; Plasma; Wettability; Cross-linking degree; Film structure; Nano films; Nitrogen ion implantations; Plasma enhanced chemical vapour depositions (PECVD); Plasma immersion ion implantation; Polar groups; Treatment time; Contact angle; Deposits; Ion bombardment; Lighting; Nitrogen; Plasma applications; Plasma enhanced chemical vapor deposition; Plasmas; Wetting; Nitrogen plasma